The Surprisingly Positive Effect of Zinc-Phthalocyanines With High Photodynamic Therapy Efficacy of Melanoma Cancer - Castro, Kelly A. D. F.; Prandini, Juliana A.; Biazzotto, Juliana Cristina; Tomé, João P. C.; da Silva, Roberto S.; Lourenço, Leandro M. O. (Frontiers in Chemistry, 2022)
Phthalocyanine (Pc) dyes are photoactive molecules that can absorb and emit light in the visible spectrum, especially in the red region of the spectrum, with great potential for biological scopes. For this target, it is important to guarantee a high Pc solubility, and the use of suitable pyridinium units on their structure can be a good strategy to use effective photosensitizers (PSs) for photodynamic therapy (PDT) against cancer cells. Zn(II) phthalocyanines (ZnPcs) conjugated with thiopyridinium units (1–3) were evaluated as PS drugs against B16F10 melanoma cells, and their photophysical, photochemical, and in vitro photobiological properties were determined. The photodynamic efficiency of the tetra- and octa-cationic ZnPcs 1–3 was studied and compared at 1, 2, 5, 10, and 20 µM. The different number of charge units, and the presence/absence of a-F atoms on the Pc structure, contributes for their PDT efficacy. The 3-(4′,5′-dimethylthiazol-2′-yl)-2,5-diphenyl tetrazolium bromide (MTT) assays on B16F10 melanoma cells show a moderate to high capacity to be photoinactivated by ZnPcs 1–3 (ZnPc 1 > ZnPc 2 > ZnPc 3). The best PDT conditions were found at a Pc concentration of 20 μM, under red light (λ = 660 ± 20 nm) at an irradiance of 4.5 mW/cm2 for 667 s (light dose of 3 J/cm2). In these conditions, it is noteworthy that the cationic ZnPc 1 shows a promising photoinactivation ratio, reaching the detection limit of the MTT method. Moreover, these results are comparable to the better ones in the literature.